Migration-enhanced energy transfer from host to dopant in Sr₂CeO₄:Eu crystal - Masalov, A.A.; Vyagin, O.G.; Ganina, I.I.; Malyukin, Yu.V. (Functional Materials, 2008)
The strontium oxycerate blue phosphor (Sr₂CeO₄) belongs to a particular class of optical materials with luminescence governed by optical transitions associated with the electron charge transfer. The uniqueness of its crystallographic structure including a chain-like sequence of luminescence centers favors the effective transfer of electron excitation energy from the matrix to impurity centers. Sr₂CeO₄ samples, both pure and activated with various Eu³⁺ concentrations have been synthesized by Pechini citrate-gel method. The luminescence spectra and luminescence decay curves of Sr₂CeO₄ and Sr₂CeO₄:Eu³⁺ have been investigated. The experiments carried out have revealed the excitonic mechanism of electron excitation energy transfer from the crystal matrix to the doping europium ions.